The Effect of Ease, Security, and Risk on Community Minat in Using Financial Technology (Fintech) Peer-To-Peer (P2P) Lending - Randyantini, Vely; Kamil, Islamiah (Dinasti International Journal of Digital Business Management, 2024)
This study aims to examine the effect of convenience, security and risk on public interest in using Financial Technology (Fintech) Peer-To-Peer (P2P) Lending. The object of this research is people in the Jakarta, Bogor, Depok, Tangerang and Bekasi (Jabodetabek) areas who have taken credit either at Peer to Peer Lending or other financial institutions. A total of 300 data were collected using survey method with convenience sampling technique. Data analysis was carried out using the SmartPLS application. The results showed that public interest in using Financial Technology (Fintech) Peer-To-Peer (P2P) Lending is influenced by convenience, security and risk.